Go put your strengths to work six powerful steps to achieve outstanding performance - Buckingham, Marcus (New York Free Press, 2007)
Research data show that most people do not come close to making full use of their assets at work. Go Put Your Strengths to Work aims to change that by kick-starting the ?strengths revolution? that began with Buckingham?s earlier books. Through a six-step, six-week experience, Go Put Your Strengths to Work shows you how to seize control of your assets and rewrite your job description under the nose of your boss.
Keywords: Employee motivation. Ability. Success. Performance-Psychological aspects